The Companion to Peace and Conflict Fieldwork
XVII, 493 p. 6 illus., 4 illus. in color.
Keywords: This unique companion is a much-needed guide for those who are embarking on field research in conflict-affected countries. In a break with academic tradition, the chapters are mainly written in the first person and contain personal accounts of the ethical and practical challenges of fieldwork. In the book, over thirty scholars reflect on the complexity of dealing with human subjects in conflict-affected contexts. This indispensable book provides insider knowledge and gives confidence to researchers - both those at the very start of their careers or during their studies, and experienced researchers who want to consider positionality, responsibility and the moral obligation of the researcher in new ways. Essential reading for students and scholars embarking upon fieldwork in International Relations, Politics, Sociology, Political Geography and Anthropology. Roger Mac Ginty is Professor at the School of Government and International Affairs, and Director of the Global Security Institute, both at Durham University, UK. He has conducted field research in Georgia, Lebanon, Uganda, Northern Ireland, Kosovo, Bosnia-Herzegovina, Sri Lanka, and the US. Roddy Brett is Senior Lecturer in Politics and International Relations at the University of Bristol, UK. During thirteen years living in Latin America, he acted as Advisor to the UNDP and the UNHCHR and as Advisor on Indigenous Affairs to the Norwegian Embassy. In 2015, he led a UN investigation into the role of the delegations of victims in the Santos-FACRC-EP peace process. Birte Vogel is Lecturer in Humanitarianism, Peace and Conflict Studies at the University of Manchester, UK. She has conducted fieldwork in Colombia, Cyprus, Bosnia-Herzegovina, India and Sri Lanka.